Protocol for measuring D-amino acid transport in mammalian cells using a fluorescent biosensor - Danisha Johal; Keeley G. Hewton; Sadie J. Gale; Amritpal S. Johal; Seth J. Parker (STAR Protocols)
Summary: The movement of amino acids into cells and organelles is facilitated by transporter proteins, which support homeostasis, metabolism, and disease progression. Here, we present a protocol to visualize amino acid transport in mammalian cells in real time using an enzyme-based biosensor. We provide instructions for plating sensor-expressing HEK293 cells, optimizing fluorescent readouts, and initiating transport measurements. Data interpretation and analysis are also discussed.For complete details on the use and execution of this protocol, please refer to Johal et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.